Lompek Paga Money in Minangkabau Custom: A Social Study and an Islamic Legal Perspective - Ulya, Azma; Fitrah, Azizah (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2025)
The lompek paga tradition in Lunto Village emerged during the youth migration of the 1980s as a customary compensation required from men marrying women from outside the village, typically in the form of five sacks of cement or an equivalent payment. This study aims to analyze the social meaning and legal status of lompek paga within the framework of Islamic law using the concept of ‘urf (custom). Using a descriptive qualitative field approach with ethnographic techniques, data were collected through interviews with niniak mamak (customary elders), community leaders, and residents. The data were analyzed thematically and triangulated to ensure validity. The findings show that lompek paga serves as a customary mechanism to maintain the social authority of niniak mamak and strengthen communal attachment to the homeland amid shifting marriage patterns caused by migration. From an Islamic legal perspective, this tradition may be categorized as ‘urf ṣāḥiḥ (valid custom) as long as it is not imposed as a marriage requirement or enforced coercively. The study demonstrates how the authority of niniak mamak has been sustained through the lompek paga institution, offering insights into the evolving relationship between customary practice and Islamic law in Minangkabau society.